2014
DOI: 10.1042/cs20140131
|View full text |Cite
|
Sign up to set email alerts
|

Novel potential targets for prevention of arterial restenosis: insights from the pre-clinical research

Abstract: Restenosis is the pathophysiological process occurring in 10-15% of patients submitted to revascularization procedures of coronary, carotid and peripheral arteries. It can be considered as an excessive healing reaction of the vascular wall subjected to arterial/venous bypass graft interposition, endarterectomy or angioplasty. The advent of bare metal stents, drug-eluting stents and of the more recent drug-eluting balloons, have significantly reduced, but not eliminated, the incidence of restenosis, which remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 162 publications
(113 reference statements)
0
28
0
Order By: Relevance
“…While the underlying mechanisms have been studied from multiple perspectives [69, 70], the N- glycoproteomics has not been very well characterized, despite that N- glycosylation is critical for correct folding, stability and mediating cell attachment [71]. Extracellular matrix (ECM) proteins has long been implicated in the pathogenesis of restenosis, and the fact that more than 90% of ECM proteins are glycosylated makes it more relevant to study carotid artery glycoproteomics [71, 72].…”
Section: Resultsmentioning
confidence: 99%
“…While the underlying mechanisms have been studied from multiple perspectives [69, 70], the N- glycoproteomics has not been very well characterized, despite that N- glycosylation is critical for correct folding, stability and mediating cell attachment [71]. Extracellular matrix (ECM) proteins has long been implicated in the pathogenesis of restenosis, and the fact that more than 90% of ECM proteins are glycosylated makes it more relevant to study carotid artery glycoproteomics [71, 72].…”
Section: Resultsmentioning
confidence: 99%
“…This leads to i ) the differentiation of intima-infiltrated monocytes into macrophages, causing them to accumulate cholesterol, become foam cells and eventually form a lipid core, and ii ) the phenotypic modulation of smooth muscle cells, switching them from a contractile to a synthetic phenotype to promote neointimal hyperplasia. The treatment of symptomatic atherosclerosis typically involves an angioplasty with stent placement but this procedure further damages the vascular endothelium and frequently triggers thrombosis and restenosis [1]. Thus, endothelial protection and repair remain key processes to consider when developing strategies to help prevent atherosclerosis and its complications [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of drug-eluting stents significantly reduces the incidence of restenosis, these drugs have not completely eliminated the occurrence of neointima. 2 A recent prospective study has shown that in patients treated with percutaneous coronary intervention, there is no significant difference in the 6-year rates of death, spontaneous myocardial infarction, quality of life, stroke, or hospitalization for unstable angina between patients receiving drug-eluting stents and those receiving contemporary bare-metal stents. 3 Moreover, managing drug-eluting stent-associated in-stent restenosis becomes an emerging challenge in clinical practice.…”
mentioning
confidence: 99%
“…3 Moreover, managing drug-eluting stent-associated in-stent restenosis becomes an emerging challenge in clinical practice. [4][5][6] Therefore, development of new therapeutic options by searching for new biological targets 2 and pharmacological agents 7 is still required. An adequate rate of ribosome biogenesis is essential for cell proliferation to meet the increased demand for protein synthesis.…”
mentioning
confidence: 99%